EDUCATIONAL QUALITY ISSUES IN THE PROCESS OF IMPLEMENTING DIGITAL TECHNOLOGIES IN THE MODERN EDUCATIONAL SYSTEM (Universal International Scientific Journal, 2026)
The article analyzes the process of introducing digital technologies in the modern education system on a scientific basis. The studied literature and national and international experience show that the effectiveness of digital education depends on the harmony of pedagogical methodology, technical infrastructure and management mechanisms. The article analyzes the main problems that cause a decrease in the quality of education - insufficient digital competence of teachers, lack of technical means and insufficient independent learning skills of students. At the same time, recommendations are presented for improving the quality of education by introducing a blended learning model, improving the qualifications of teachers and creating modern educational resources.
Keywords: : Digital education, quality of education, pedagogical competence, technical infrastructure, blended learning.